Cetuximab: Its Use in Combination with Radiation Therapy and Chemotherapy in the Multimodality Treatment of Head and Neck Cancer - Wagner, Timothy D.; Yang, Gary Y. (Recent Patents on Anti-Cancer Drug Discovery, 2008)
Dimerization of epidermal growth factor receptor (EGFR) on the cell membrane of tumor cells has been implicated in triggering a complex signal cascade that leads to increased tumor proliferation and survival. Cetuximab is a human-murine chimeric monoclonal antibody designed to target EGFR and competitively inhibit dimerization by circulating ligands. By this mechanism, it works to prevent this signal cascade thus hindering tumor proliferation. Cetuximab has been shown in a randomized phase III clinical trial to significantly increase overall survival when it is added to radiation therapy in the treatment of locally advanced squamous cell carcinoma of the head and neck. In this manuscript, the mechanism of cetuximab with its associated patents is reviewed, with its role with chemotherapy and radiation in the management of head and neck cancer along with future directions of this targeted cancer therapy.
Keywords: Cetuximab